2020
DOI: 10.1029/2020jd032706
|View full text |Cite
|
Sign up to set email alerts
|

Global Importance of Hydroxymethanesulfonate in Ambient Particulate Matter: Implications for Air Quality

Abstract: Sulfur compounds are an important constituent of particulate matter, with impacts on climate and public health. While most sulfur observed in particulate matter has been assumed to be sulfate, laboratory experiments reveal that hydroxymethanesulfonate (HMS), an adduct formed by aqueous phase chemical reaction of dissolved HCHO and SO 2 , may be easily misinterpreted in measurements as sulfate. Here we present observational and modeling evidence for a ubiquitous global presence of HMS. We find that filter sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 82 publications
0
50
1
Order By: Relevance
“…Recent work also identified the potential of IO x ion chemistry to lead to measurement interferences (Dörich et al, 2021) and of the detection of acid gases, which could impact the measured HOCl : HCl ratio. Furthermore, rapid interconversion of halogen species on inlet walls has been reported that could also impact the measured HOCl : HCl ratio (Neuman et al, 2010).…”
Section: Inorganic Chlorine Gases (Cl Y )mentioning
confidence: 99%
“…Recent work also identified the potential of IO x ion chemistry to lead to measurement interferences (Dörich et al, 2021) and of the detection of acid gases, which could impact the measured HOCl : HCl ratio. Furthermore, rapid interconversion of halogen species on inlet walls has been reported that could also impact the measured HOCl : HCl ratio (Neuman et al, 2010).…”
Section: Inorganic Chlorine Gases (Cl Y )mentioning
confidence: 99%
“…3 or SO −2 3 can react with a variety of aldehydes to form hydroxyalkylsulfonates (Olson and Hoffmann, 1989). Of particular interest has been the S(IV) reaction with HCHO to produce hydroxymethanesulfonate (HMS; HOCH 2 SO − 3 ; Munger et al, 1986). The formation of HMS is strongly dependent on drop acidity, which increases rapidly at higher pH values due to the increased partitioning of S(IV) to HSO − 3 and SO 2− 3 (Rao and Collett, 1995).…”
Section: Hso −mentioning
confidence: 99%
“…10.55 298.15 T −1 , K 1 = 1.3 × 10 −2 e 6.75 298.15 T −1 , K 2 = 6.31 × 10 −8 e 5.05 298.15 T −1 298.15 T −1 , K 3 = 2.2 × 10 −12 e 12.52 298.15 T −1 (Alexander et al, 2012). This iterative calculation is updated to use Newton's method in order to arrive at a consistent result (Moch et al, 2020). To implement Newton's method, the equilibrium expressions for the concentrations of each soluble semivolatile ion (SSVI) in terms of H + and the derivatives for these equilibrium expressions are each solved explicitly so that Newton's method equation is in the form of…”
Section: Introductionmentioning
confidence: 99%
“…To reflect the impact of soluble nonvolatile cations on cloud water pH, we assume that total G. Luo et al: Improved wet processes in GEOS-Chem and global validations amount of soluble nonvolatile cations associated with aerosol thermodynamics (SNVC) is 25 % of sulfate. We also consider the contribution of calcium and magnesium based on simulated dust mass in GC12, assuming that 3 % of dust mass is soluble calcium and 0.6 % is soluble magnesium (Farlie et al, 2010;Moch et al, 2020), to SNVIs:…”
Section: Introductionmentioning
confidence: 99%